Migration Of Boiler Drum Temperature (BDT) Into Aspen Dynamics Environment For Teaching And Research Purposes - Rosli, Nur Hasniena Mohd (Universiti Sains Malaysia, 2017)
Dynamic simulation and modelling has turned into a need to process control engineers. This is due to dynamics and steady state study are in line with the primary objective of process control which is to maintain a process at the desired operating conditions. In this study, migration of the Boiler Drum Temperature was done using Aspen Plus for steady state condition. Sensitivity analysis was done to analyse the effect of input changes on the output of the process. Then, the simulation was exported to Aspen Dynamic platform to study the dynamics of the system, whereby control loops are added and studied. The overall control performance was also evaluated by introducing disturbances in the feed streams of the process and introducing the tuning parameter. Validation of the simulation was done with the actual experimental data. The performance of the simulation for the temperature is much faster compared to the actual process but for level it has slower response. In addition, the controller performance is improved by tuning using Z-N. It became faster to get to the desired set point compared to normal PID.